2014
DOI: 10.2147/ceor.s63323
|View full text |Cite
|
Sign up to set email alerts
|

Pain severity and the economic burden of neuropathic pain in the United States: BEAT Neuropathic Pain Observational Study

Abstract: BackgroundAs with many chronic conditions, patients with neuropathic pain (NeP) are high consumers of health care resources. However, limited literature exists on the economic burden of NeP, including its impact on productivity. The aim of this study was to characterize health care resource utilization, productivity, and costs associated with NeP by pain severity level in US adults.MethodsSubjects (n=624) with painful diabetic peripheral neuropathy, human immunodeficiency virus-related peripheral NeP, post-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 28 publications
3
42
0
Order By: Relevance
“…Similarly, Chevalier et al ,35 in a modeling study, concluded that from the perspective of the payer in Belgium pregabalin offers a slight increase in quality of life in the populations studied in comparison with standard care. Other studies have corroborated the reduction of work‐related costs in patients treated with pregabalin 36. These findings are consistent with ours.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, Chevalier et al ,35 in a modeling study, concluded that from the perspective of the payer in Belgium pregabalin offers a slight increase in quality of life in the populations studied in comparison with standard care. Other studies have corroborated the reduction of work‐related costs in patients treated with pregabalin 36. These findings are consistent with ours.…”
Section: Discussionsupporting
confidence: 93%
“…It is one of the series with the highest number of subjects studied, which should be interpreted as a study strength 31, 32, 33, 34, 35, 36. However, it should be noted that without appropriate standardization of patient characteristics, as well as in the number and extent of the variables studied, the results obtained should be interpreted with caution, and care should be taken in the external validation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Despite spending more on healthcare resources, this study showed that participants with NeP did not experience better outcomes or satisfaction than those without NeP. Similarly, Schaefer et al (2014) reported that participants with greater NeP severity use more healthcare resources in terms of both direct and indirect costs. They estimated that the adjusted total mean annualized direct cost to payers was $27,259 per participant based on 624 established patients with NeP.…”
Section: The Effective Use Of Healthcare Resourcesmentioning
confidence: 61%
“…chronic pain, depression, mediation effect, neuropathic pain, nurse, nursing, pain, pain nursing practice, quality of life Kong, patients with NeP had more severe pain intensity, more pain descriptors, worse sleep quality and more lost workdays than those chronic pain patients without NeP (Inoue et al, 2017;Wong, Choi, & Cheung, 2018). In Europe and America, poor QoL in patients with NeP constitutes a heavy illness burden for patients and their caregivers or family members (Liedgens, Obradovic, De Courcy, Holbrook, & Jakubanis, 2016;Schaefer et al, 2014). As a result, improving QoL of patients with NeP is an important issue in nursing practice.…”
Section: Introductionmentioning
confidence: 99%